2021
DOI: 10.1097/mcc.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

Role of ketones, ketogenic diets and intermittent fasting in ICU

Abstract: Purpose of reviewTo summarize the clinical evidence for beneficial effects of ketones, ketogenic diets and intermittent fasting in critical illness, and to review potential mechanisms behind such effects. Recent findingsRecent evidence demonstrates that activation of a metabolic fasting response may be beneficial to recover from critical insults. Potential protective mechanisms are, among others, activation of ketogenesis and of damage removal by autophagy. Novel feeding strategies, including ketone supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 52 publications
0
11
0
10
Order By: Relevance
“…Increasing evidence suggests a potentially protective effect of enhancing ketone availability during critical illness [ 1 ]. Whereas ketone bodies may serve as vital and more energy-efficient energy substrate than glucose or fatty acids, ketones may also exert signaling functions leading to anti-inflammatory effects and activation of recovery processes such as muscle regeneration and autophagy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests a potentially protective effect of enhancing ketone availability during critical illness [ 1 ]. Whereas ketone bodies may serve as vital and more energy-efficient energy substrate than glucose or fatty acids, ketones may also exert signaling functions leading to anti-inflammatory effects and activation of recovery processes such as muscle regeneration and autophagy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, studies performed in animal models of sepsis and brain injury have demonstrated protective effects of providing ketones or ketogenic diets [ 3 , 4 ]. However, human evidence remains scarce, with only a few small randomized controlled trials (RCTs) suggesting improved blood glucose control by ketone supplementation or ketogenic diets [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, efficacy and safety remain to be studied. Apart from intermittent feeding strategies, ketogenic diets or ketone supplementation could be beneficial [ 85 ]. Although ketogenic diets have been used in selected patients including patients with refractory status epilepticus, the efficacy and safety of ketogenic diets or ketone supplements for general critically ill patients remain to be studied [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…One indirect calorimetry study found that AKI patients, both septic and nonseptic, were not given enough lipid to support measured lipid oxidation rates, while carbohydrates were given more than actual glucose oxidation rates [99]. Thus, alternative approaches could include limiting the glycemic load or changing the delivery of feeds to allow for adequate periods of fasting capable of enhancing FAO, ketogenesis and autophagy [100 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has extensively examined the timing of feeding initiation in ICU patients, however an organized approach to comparing an intermittent versus continuous feeding protocol and by extension the importance of fasting periods in critically ill patients has yet to be undertaken. Several small noninferiority RCTs reported favorably on clinical endpoints such as gastrointestinal distress and aspiration pneumonia for those receiving intermittent feeds compared to those continuously fed [100 ▪ ,101 ▪ ]. However, the small sample sizes, lack of harder endpoints, inconsistent reporting on metabolic variables, and heterogeneity in feed and insulin administration protocols limit our ability to make broader conclusions about the effect of fasting duration on optimizing metabolism to survive critical illnesses such as sepsis.…”
Section: Introductionmentioning
confidence: 99%